Substitution effect of super hydrophobic units: A new strategy to design deep blue fluorescent emitters. (April 2017) - Li, Ke; Liu, Ming; Yang, Shuai; Chen, Yantong; He, Yaowu; Murtaza, Imran; Goto, Osamu; Shen, Clifton; Meng, Hong; He, Gufeng
Abstract: Fluorescent deep-blue emitters consisting of arylamine chrysene have attracted immense commercial interest in organic light-emitting devices (OLEDs). Herein, we endeavor to design emitters with super hydrophobic groups, namely trifluoromethoxy (OCF3 ) or trifluoromethylsufanyl (SCF3 ) substituted on 6, 12-diarylamine chrysene. Surprisingly, the new materials show highly efficient and substantial blue shift in fluorescence spectra with more pure color quality, higher thermostability and better moisture resistant properties. Astonishing electroluminescence performance is envisioned by promoting the molecular design based on experience and theoretical calculations along with the single crystal X-Ray analysis. The CIE coordinate values for 6, 12-diamine- N, N, N ′, N ′- tetra ( p- trifluoromethoxyphenyl)chrysene (DATPC-OCF3 ) and 6, 12-diamine- N, N, N ′, N ′- tetra ( p- trifluoromethylsulfanylphenyl)chrysene (DATPC-SCF3 ) are (0.14, 0.09) and (0.15, 0.06), respectively, which exactly match with the National Television System Committee (NTSC) and High-Definition Television requirements for unprecedented deep-blue emission. Graphical abstract: Highlights: Super hydrophobic deep blue OLED fluorescence materials is a new concept. Introduced super hydrophobic groups achieved better moisture resistant properties, and deeper blue simultaneously. Astonishing performance is envisioned by molecular design based on theoretical calculations and the single crystal X-Ray. The CIE value for new materials are exactly match with the High-Definition Television requirements for deep blue emission.